Barriers to Physical Activity in Spanish Children and Adolescents: Sex and Educational Stage Differences - Delfa-De-La-Morena, José Manuel; Bores-García, Daniel; Solera-Alfonso, Adrián; Romero-Parra, Nuria (Frontiers in Psychology, 2022)
According to worrisome childhood obesity and inadequate physical activity (PA) levels worldwide, especially exacerbated in adolescents girls, this work aimed to identify sex and educational stage differences in barriers to meet PA requirements and international guidelines in Spanish children and adolescents considering the entire educational pathway (primary, secondary, and college). The Short Form of the International PA Questionnaire and the Scale of Perceived Barriers were administered to primary, secondary, and college education students (13,491 boys and 13,238 girls, 9–19 yrs). Two-way ANOVA was performed to analyze barriers to PA according to sex and educational stage with physical status as covariate. Higher disliking and time barriers were reported by females (1.5 ± 1.2 and 3.2 ± 1.5 points) in comparison to males (1.2 ± 1.0 and 2.8 ± 1.4), while primary students showed lower disliking and time (1.2 ± 1.0 and 2.8 ± 1.5) and higher safety (3.1 ± 1.8) constraints in comparison to secondary (1.4 ± 1.1, 3.1 ± 1.4, and 2.8 ± 1.7) and college (1.5 ± 1.2, 3.2 ± 1.5, and 2.8 ± 1.6; p < 0.05 for all comparisons). College females showed higher disliking (1.7 ± 1.2) and time (3.5 ± 1.4) barriers than secondary females (1.5 ± 1.2 and 3.3 ± 1.4; p < 0.05). Sex and educational stage were determinant for time and dislike of PA barriers, which were rated higher by female students in comparison to their male counterparts and from primary education onwards. Altogether this, suggests promotion strategies should carefully consider girls and the step into secondary school.